Bangsamoro society and culture [Book review] - Ortega, Christine Godinez; Kamlian, Jamail A. (2006)
Bangsamoro society and culture by Jamal A. Kamlian, published by the OVCRE-Iligan Center for Peace Education and Research MSU-Iligan Institute of Technology, 1999, 167pp